The role of family communication: Family health and welfare during pandemic covid - Maulana Rezi Ramadhana; Dewi Kurniasih Soedarsono; Retno Setyorini (Universitas Padjadjaran, 2022)
The Covid-19 pandemic causes psychological stress, such as fear and anxiety, and requires exceptional recovery. Such conditions can lead to mental disorders and the risk of developing physical health even in a healthy person without a medical history. The purpose of this study was to find a theoretical model of the relationship between family communication, physical resilience, and family economic well-being, to describe the role of the family in maintaining family health during the pandemic, and describe the role of the family in maintaining family economic well-being during the COVID-19 pandemic. This study uses a quantitative method with a descriptive and correlational approach. The population in Rancatungku Village, Bandung Regency, West Java Province, is an area affected by COVID-19, with a total sample of 420 respondents. The results obtained that Family Communication affects Family Physical Resilience, with an effect of 40% due to positive communication and direct interaction with family members as a protective factor for facilities and the needs of family members. The existence of an atmosphere of mutual protection means that the family must be a safe, comfortable, and reassuring place for all its members. Family communication does not affect Family Economic Resilience, with a contribution of only 10%; this is related to the strategy and quick decision-making by the family to think about recovery from the situation. Family Communication affects the Pandemic Impact on Families by 80%. Communication is critical as a protective function of changes that arise from the pandemic and is seen as a family management system. In addition, the pandemic was declared to impact work activities and social activities but had no impact on activities at home or emotional and physical activities.